2016
DOI: 10.1158/1078-0432.ccr-16-0148
|View full text |Cite
|
Sign up to set email alerts
|

TransCONFIRM: Identification of a Genetic Signature of Response to Fulvestrant in Advanced Hormone Receptor–Positive Breast Cancer

Abstract: Purpose Fulvestrant is an estrogen receptor (ER) antagonist and an approved treatment for metastatic estrogen receptor positive (ER+) breast cancer. With the exception of ER levels, there are no established predictive biomarkers of response to single agent fulvestrant. We attempted to identify a gene signature of response to fulvestrant in advanced breast cancer. Experimental Design Primary tumor samples from 134 patients enrolled in the phase III CONFIRM study of patients with metastatic ER+ breast cancer c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…TFAP2C is a regulator of ER transcriptional activity and luminal differentiation (Cyr et al, 2015). Moreover, we recently showed that TFAP2C expression was highly associated with decreased progression free survival in metastatic ER + breast cancer (Jeselsohn et al, 2016). To validate that TFAP2C is a ER-mutant transcriptional target and an essential gene for mutant cell growth in HD conditions, we first confirmed mutant induced upregulation of TFAP2C mRNA and protein levels (Figure S5B-S5C).…”
Section: Resultsmentioning
confidence: 99%
“…TFAP2C is a regulator of ER transcriptional activity and luminal differentiation (Cyr et al, 2015). Moreover, we recently showed that TFAP2C expression was highly associated with decreased progression free survival in metastatic ER + breast cancer (Jeselsohn et al, 2016). To validate that TFAP2C is a ER-mutant transcriptional target and an essential gene for mutant cell growth in HD conditions, we first confirmed mutant induced upregulation of TFAP2C mRNA and protein levels (Figure S5B-S5C).…”
Section: Resultsmentioning
confidence: 99%
“…Through its role as a pioneer factor for oestrogen receptor, higher levels of FOXA1 protein may increase cellular sensitivity to oestrogen. While FOXA1 expression has been linked with positive clinical outcome 2729 , high levels of FOXA1 have recently been associated with poor outcome, metastasis, decreased response to fulvestrant, and endocrine resistance 26,30,31 . Identification of FOXA1 alterations in patients undergoing hormone therapy may thus be important for recognizing mechanisms for resistance to therapy and tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…In the TransCONFIRM substudy, genome-wide transcrip-tomic analysis was conducted on primary tumor samples from 134 patients with Affymetrix microarrays (Santa Clara, CA, USA). 68 High expression of most genes in the EGF-signaling pathway and FOXA1 transcription-factor network strongly predicted decreased PFS. An exploratory multivariate Cox analysis identified a set of 37 genes, among them the known regulator of ER activity TFAP2C , whose expression was independently associated with PFS.…”
Section: Efficacy Studies For Fulvestrant As Monotherapy or In Combinmentioning
confidence: 98%
“…In the TransCONFIRM substudy, genome-wide transcrip-tomic analysis was conducted on primary tumor samples from 134 patients with Affymetrix microarrays (Santa Clara, CA, USA) 68. High expression of most genes in the EGF-signaling pathway and FOXA1 transcription-factor network strongly predicted decreased PFS.…”
Section: Efficacy Studies For Fulvestrant As Monotherapy or In Combinmentioning
confidence: 99%